Codesigning a Culture-Centered Age-Friendly Community for Māori Kaumātua: Cultural Principles and Practices. (7th July 2022) - Simpson, Mary Louisa; Oetzel, John; Wilson, Yvonne; Nock, Sophie; Johnston, Kirsten; Reddy, Rangimahora
Abstract: Objectives: This study examined a Māori (Indigenous people of Aotearoa New Zealand) age-friendly housing development. Two Māori community groups worked with multiple stakeholders to codesign a culture-centered, kaumātua (older adults) urban housing community. The purpose was to identify codesign and culture-centered principles in the development. Methods: Kaupapa Māori (Māori-centered) and participatory research methodologies guided the culture-centered research design. Data collection included 27 interviews with 19 residents and 12 organizational stakeholders; three focus groups with residents' families, service providers, and nonresident kaumātua ( n = 16); and project documents. Data analysis used the framework method. Results: Three codesign process themes emerged: (a) Kaumātua-centered vision; (b) realizing the vision; and (c) living the shared vision. Discussion: Accounting for cultural practices in codesigning age-friendly and culture-centered housing for and with Indigenous older adults helps meet their cultural, social, health, and economic needs. The research offers a practical pathway to developing age-friendly housing environments for Māori kaumātua, their communities, wider society, and other Indigenous people.